Managing Job Satisfaction In Malaysia - Tee, Mei Ghee (2006)
The objective for this research paper is to explore the factors of job satisfaction. Another objective is to find out the relationship of job satisfaction with pay, security, social, supervision and growth in a manufacturing organization.